Efficacy of valdoxan in the prevention and treatment of post-stroke depression - Dina Rustemovna Khasanova; Yu V Zhitkova; A A Safiullina (Неврология, нейропсихиатрия, психосоматика, 2012)
The efficacy of valdoxan (agomelatine) used to prevent and treat post-stroke depression was analyzed. The study enrolled 49 patients (21 men and 28 women; mean age 61+5.5years) in the acute period of ischemic stroke in different vascular basins (a study group). A control group included 50 patients (24 men and 26 women; mean age 64+4.8 years) who were comparable with the study group of patients and who did not receive valdoxan. The duration of a follow-up was 6 months. During valdoxan therapy, there were better changes in recovery with a rapider regression of neurological disorders in patients with moderate stroke as compared with the control group (according to the National Institute of Health Stroke Scale (NIHSS). The administration of valdoxan prevents depression, sleep disorders, pain syndromes, and cognitive impairments in the acute and early rehabilitation period of stroke.